Oligomerization of Prph2 and Rom1 is essential for photoreceptor outer segment formation - Zulliger, Rahel (Hum Mol Genet, 2018)
Mutations in peripherin 2 (PRPH2, also known as Rds), a tetraspanin protein found in photoreceptor outer segments (OSs), cause retinal degeneration ranging from rod-dominant retinitis pigmentosa (RP) to cone-dominant macular dystrophy (MD). Understanding why some Prph2 mutants affect rods while others affect cones remains a critical unanswered question. Prph2 is essential for OS structure and function and exhibits a very specific pattern of oligomerization with its homolog Rom1. Non-covalent Prph2/Rom1 homo- and hetero-tetramers assemble into higher-order covalently linked complexes held together by an intermolecular disulfide bond at Prph2-C150/Rom1-C153. Here we disrupt this crucial bond using a C150S-Prph2 knockin mouse line to study the role of Prph2 higher-order complex formation. We find that C150S-Prph2 traffics to the OS, interacts with Rom1 and forms non-covalent tetramers, but alone cannot support normal OS structure and function. However, C150S-Prph2 supports the initiation or elaboration of OS disc structures, and improves rod OS ultrastructure in the presence of wild-type (WT) Prph2 (i.e. Prph2(C150S/+) versus Prph2(+/−)). Prph2(C150S/+) animals exhibit haploinsufficiency in rods, but a dominant-negative phenotype in cones, suggesting cones have a different requirement for large Prph2 complexes than rods. Importantly, cone but not rod function can be improved by the addition of one Prph2(Y141C) allele, a mutation responsible for pattern dystrophy owing to the extra cysteine. Combined these findings show that covalently linked Prph2 complexes are essential for OS formation, but not for Prph2 targeting to the OS, and that cones are especially sensitive to having a broad distribution of Prph2 complex types (i.e. tetramers and large complexes).